NON SURGICAL A BIOLOGICAL; APPROACH - Maita Véliz, Luis (2004)
Periodontal therapy can be broadly classified as surgical and non surgical therapy. Non surgical therapy includes: patient's motivation, plaque control, supra and subgigival acaling, root planning and complementary use of chemical agents. Non surgical therapy is an effective method of periodontal therapy. Longitudinal studies have found that non surgical therapy was effective for single rooted teeth, and multi rooted teeth and also, in shallow deep pockets. It must be pointed out that non surgical therapy may not be effective in some sites and even in some patients, therefore in must be recognized that after reevaluation appointments it should be performed an appropriate surgical therapy.